CHARACTERISTICS WANPRESTASI AND ONRECHTMATIGE DAADAND THE CONSEQUENCES OF THE LAW - SURYOUTOMO, MARKUS (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Onrechtmatigedaad and wanprestasi claims always rely on a contractual relationship between parties, giving birth to legal rights and obligations. Rights and obligations here are manifested by an achievement. When an achievement is not fulfilled or carried out in accordance with the contents of the agreement, it is called a default. While the act of violating the law the starting point of the lawsuit is the interests of certain parties who are harmed by the actions of other parties, even though between the parties there is nocontractual civil law relationship. In this case, the basis for the lawsuit is sufficient to prove whether the perpetrator's actions have actually harmed the other party. In other words, filing a lawsuit in violation of the law is solely oriented to the consequences caused by other parties experiencing losses. Petitum Lawsuit Defaults the plaintiff's demands in the form of: Granting the plaintiff's claim; Stating the Defendant has a Default, Punishing the Defendant to return the Principal, Interest and Profits to be obtained. In a Lawsuit for Violating the Plaintiff's Lawsuit; Stating the Defendant has committed an illegal act; Punish Defendant to pay compensation in the form of Material Compensation and Moriel Compensation. the merging of Unlawful Acts with default in one claim violates the procedural code of conduct because both must be resolved separately